2022
DOI: 10.3389/fgene.2022.1016416
|View full text |Cite
|
Sign up to set email alerts
|

Allelic diversity of the pharmacogene CYP2D6 in New Zealand Māori and Pacific peoples

Abstract: The enzyme cytochrome P450 2D6 (CYP2D6) metabolises approximately 25% of commonly prescribed drugs, including analgesics, anti-hypertensives, and anti-depressants, among many others. Genetic variation in drug metabolising genes can alter how an individual responds to prescribed drugs, including predisposing to adverse drug reactions. The majority of research on the CYP2D6 gene has been carried out in European and East Asian populations, with many Indigenous and minority populations, such as those from Oceania,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Since *1 , *35 , and *27 are normal function alleles, the predicted phenotype was UM regardless of which allele is duplicated. The phenotype of sample B2 ( *4/*32 ) was indeterminate due to the uncertain function of the *32 allele (Phasing was confirmed through long read Nanopore sequencing; protocols as described in ( Hitchman et al, 2022 )). With the presence of a non-functional *4 allele, B2 is expected to be either IM or PM.…”
Section: Resultsmentioning
confidence: 99%
“…Since *1 , *35 , and *27 are normal function alleles, the predicted phenotype was UM regardless of which allele is duplicated. The phenotype of sample B2 ( *4/*32 ) was indeterminate due to the uncertain function of the *32 allele (Phasing was confirmed through long read Nanopore sequencing; protocols as described in ( Hitchman et al, 2022 )). With the presence of a non-functional *4 allele, B2 is expected to be either IM or PM.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, the overall Indigenous participation in GWAS cohorts was just ∼0.02%. A recent study by Hitchman et al have reported a rare uncertain function allele CYP2D6 *71, with a high prevalence of 8.9% among New Zealand Māori and Pacific peoples demonstrating the need for more genetic studies in distinct ethnic groups ( Hitchman et al, 2022 ). The lack of reference variant data for these minority groups has hampered clinical variant analysis efforts focused on these populations, resulting in the imprecise interpretation of clinical results and thereby directly impacting the access of these populations to equitable health outcomes ( Garrison et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%